Some problems of science-technology strategies through comparison with science-technology policies - Long, Hoang Xuan; Chi, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Science-technology strategies and science-technology policies are different from their visions, long term or short term, scopes of interests, global or sectorial, applied commonly for the whole science-technology sector or for specifically selected topics. These aspects were dealt in numerous documents. Nevertheless this paper tries to clarify certain aspects. Here, the authors note some remarkable comparisons on the roles and their meanings, indicators in objectives, opposite sides in building related documents and evaluating outcomes of their main components. Code: 19050602 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">